2014
DOI: 10.2298/jsc140709084s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antimicrobial and antioxidative activity of some new isatin derivatives

Abstract: The isatin derivatives, Schiff bases, were synthesized by the reaction of isatin and various substituted primary amines and characterized by several spectroscopic methods. Investigation of the antimicrobial activity of the synthesized compounds was performed by the agar dilution method, against different strains of bacteria and one fungus. The antioxidative activity of the synthesized compounds was also determined. Some of the compounds showed significant activity against the selected strains of microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Hence different derivatives of isatin like hydrazine derivatives, acetone and ketone derivatives, thiosemicarbazone derivates etc are being explored for their potential against tuberculosis, leprosy, fungal, viral and bacterial infections and Trypnosomiasis. Besides this, antioxidative activity of Isatin derivatives has also been reported [18].…”
Section: Mechanism Of Actionmentioning
confidence: 90%
See 1 more Smart Citation
“…Hence different derivatives of isatin like hydrazine derivatives, acetone and ketone derivatives, thiosemicarbazone derivates etc are being explored for their potential against tuberculosis, leprosy, fungal, viral and bacterial infections and Trypnosomiasis. Besides this, antioxidative activity of Isatin derivatives has also been reported [18].…”
Section: Mechanism Of Actionmentioning
confidence: 90%
“…The most potent antimicrobial compound was found to be 1,3dihydro-3-[(5-mercapto-1,3,4-thiadiazol-2-yl)imino]-2H--indol-2-one. All the isatin derivatives showed better antibacterial activity against gram positive bacteria as compared to gram negative bacteria [18]. Antifungal activity of 12 organic compounds derived from amino alcohols was measured.…”
Section: Antimicrobial Properties Of Functionally Substituted Chemicamentioning
confidence: 99%
“…The biological data used in this study were antimicrobial activity against Ecoli, (in terms oflog MIC), of a set of 86 isatin derivatives [29][30][31][32][33][34][35]. Firstly, the outlier data was removed from the data set according to principle component analysis, it was shown in Fig.…”
Section: Data Setmentioning
confidence: 99%
“…1 Recently, a published study on the antimicrobial activity of isatin derivatives, performed by the agar dilution method, against selected strains of bacteria and one fungus, as well as on their antioxidative activity, showed that the examined isatin derivatives possessed moderate to significant activity. 2 Derivatives of isatin, as well as of its Schiff and Mannich bases, have already been reported to show a variety of biological activities, such as antibacterial, 3 antifungal 4 and anti-HIV activities. 5,6 However, to the best of our knowledge, there have hitherto been no reports on the solvatochromic effects of isatin derivatives.…”
Section: Introductionmentioning
confidence: 99%